Representation of Visuotactile Space in the Split Brain - Spence, Charles; Kingstone, Alan; Shore, David I.; Gazzaniga, Michael S. (Psychological Science, 2001)
Recent neurophysiological research in the monkey has revealed bimodal neuronal cells with both tactile receptive fields on the hand and visual receptive fields that follow the hands as they move, suggesting the existence of a bimodal map of visuotactile space. Using a cross-modal congruency task, we examined the representtion ofvisuotactile space in normal people and in a split-brain patient (J. W.) as the right arm assumed different postures. The results showed that the congruency effects from distracting lights followed the hand around in space in normal people, but failed to do so in the split-brain patient when the hand crossed the midline. This suggests that cross-cortical connections are required to remap visual space to the current hand position when the hand crosses the midline.